The Influence of Brief Counseling on Work Motivation and Implementation of Patient Safety Culture in Staff at Ramdani Husada Clinic - Ika Retnani; Agusta Dian Ellina; Yenny Puspitasari (STRADA : Jurnal Ilmiah Kesehatan, 2024)
The application of work motivation and patient safety culture is one facet of work culture, which is an organizational management concept. Additional evidence regarding the use and efficacy of counseling in the workplace can be obtained by understanding how different stakeholders use it. The purpose of this study is to ascertain how brief counseling affects staff members' job motivation and adoption of the Ramdani Husada Clinic's patient safety culture. Quantitative research employing a "nonequivalent control group design" methodology is the methodology employed. A sample of sixty-three individuals was selected using a non-random sampling technique. Three statistical tests are used in the data analysis technique: multivariate analysis of variance (MANOVA), paired sample t-test, and independent sample t-test. The findings of the study demonstrated that.